Feelings for the Suffering of Others and the Environment: Compassion Fosters Proenvironmental Tendencies. (August 2016) - Pfattheicher, Stefan; Sassenrath, Claudia; Schindler, Simon
Recent research has shown that compassionate feelings for the suffering environment promote conservation of nature. We extend this notion and relate compassion for suffering humans to proenvironmental tendencies. The proposed relation should hold true as compassion elicits moral actions and judgments across different moral domains which should also be applicable to the environment. Therefore, we expect compassion for other humans to relate positively to proenvironmental tendencies. Two studies were conducted to test this assumption. Study 1 included three independent samples (final N = 2, 096) and several measures of proenvironmental tendencies. Results revealed that compassion was indeed positively related to proenvironmental values, proenvironmental intentions, and reported donations to nature or environmental organizations. In Study 2, we experimentally tested and found a causal path between compassion for humans and proenvironmental intentions. Implications for climate change and protection of nature are discussed.